Mobile learning for history and cultural heritage education in Indonesia: a systematic review - Salvetri Salvetri; Jeki Haryanto (Indonesian Counselor Association (IKI), 2025)
History education in Indonesia faces declining student engagement despite the increasing vulnerability of historical and cultural heritage. Mobile technologies have been proposed as a potential solution, yet empirical evidence remains fragmented. This study reviews empirical research on the use of mobile devices for history and cultural heritage learning in Indonesia, focusing on research design, technology, pedagogy, and learning outcomes. Following the PRISMA 2020 framework, a systematic search was conducted in Scopus on 22 December 2025 using Boolean search terms based on the PICOS framework. Of 5,952 records identified, 14 studies met the inclusion criteria after removing duplicates, ineligible records, and studies that did not meet the specified requirements. Eligible studies were open-access, peer-reviewed, English-language articles published between 2021 and 2025 and based on primary field research in Indonesian educational contexts. The findings indicate that augmented reality (AR) and mobile application development were the dominant technologies, while most studies focused on design and development. Overall, the studies reported positive effects on student motivation, usability, and knowledge acquisition. However, assessments of historical thinking skills and long-term learning outcomes were rarely conducted. This review provides an evidence map of the field and highlights the need for theory-based, controlled experimental research with long-term outcome measurements.